MULTILEVEL SEISMIC ON UPPER KAMA POTASH DEPOSIT: THEORY AND PRACTICAL SOLUTIONS - Chugayev, A.V.; Sanfirov, I.A. (Perm Federal Research Centre Journal, 2014)
Water-soluble mineral deposits research with single seismic methods have some limitations, which can’t be avoided within the scope of single technique. As a solution to this problem the paper proposes integrated use of several types of waves (reflected, refracted and surface), recorded during the standard reflection method. The basic theory of seismic techniques included in the proposed complex is provided to help the layman understand the seismic technologies. The second part shows the most significant examples of the implementation of technology while studying objects related to the development and operation of Upper Kama potash deposit.